A multicenter study on the quantification of liver iron concentration in thalassemia patients by means of the MRI T2* technique - Xu, Fengming; Peng, Yuzhao; Xie, Hanhong; Liang, Bumin; Yang, Gaohui; Zhao, Fanyu; Liu, Yu; Peng, Peng (Frontiers in Medicine, 2023)
Objective To investigate the feasibility and accuracy of quantifying liver iron concentration (LIC) in patients with thalassemia (TM) using 1.5T and 3T T2* MRI. Methods 1.5T MRI T2* values were measured in 391 TM patients from three medical centers: the T2* values of the test group were combined with the LIC (LICF) provided by FerriScan to construct the curve equation. In addition, the liver 3T MRI liver T2* data of 55 TM patients were measured as the 3T group: the curve equation of 3T T2* value and LICF was constructed. Results Based on the test group LICF (0.6–43 mg/g dw) and the corresponding 1.5T T2* value, the equation was LICF = 37.393T2*∧(−1.22) (R2 = 0.971; P < 0.001). There was no significant difference between LICe − 1.5T and LICF in each validation group (Z = −1.269, −0.977, −1.197; P = 0.204, 0.328, 0.231). There was significant consistency (Kendall's W = 0.991, 0.985, 0.980; all P < 0.001) and high correlation (rs = 0.983, 0.971, 0.960; all P < 0.001) between the two methods. There was no significant difference between the clinical grading results of LICe − 1.5T and LICF in each validation group (χ2 = 3.0, 4.0, 2.0; P = 0.083, 0.135, 0.157), and there was significant consistency between the clinical grading results (Kappa's K = 0.943, 0.891, 0.953; P < 0.001). There was no statistical correlation between the LICF (≥14 mg/g dw) and the 3T T2* value of severe iron overload (P = 0.085). The LICF (2–14 mg/g dw) in mild and moderate iron overload was significantly correlated with the corresponding T2* value (rs = −0.940; P < 0.001). The curve equation constructed from LICF and corresponding 3T T2* values in this range is LICF = 18.463T2*∧(−1.142) (R2 = 0.889; P < 0.001). There was no significant difference between LICF and LICe − 3T in the mild to moderate range (Z = −0.523; P = 0.601), and there was a significant correlation (rs = 0.940; P < 0.001) and significant consistency (Kendall's W = 0.970; P = 0.008) between them. LICe − 3T had high diagnostic efficiency in the diagnosis of severe, moderate, and mild liver iron overload (specificity = 1.000, 0.909; sensitivity = 0.972, 1.000). Conclusion The liver iron concentration can be accurately quantified based on the 1.5T T2* value of the liver and the specific LIC-T2* curve equation. 3T T2* technology can accurately quantify mild-to-moderate LIC, but it is not recommended to use 3T T2* technology to quantify higher iron concentrations.